Molluscum Contagiosum Virus Protein MC005 Inhibits NF-kappa B Activation by Targeting NEMO-Regulated I kappa B Kinase Activation - Brady,G; Haas,DA; Farrell,PJ; Pichlmair,A; Bowie,AG (Journal of Virology, 2017)
Molluscum contagiosum virus (MCV), the only known extant human-adapted poxvirus, causes a long-duration infection characterized by skin lesions that typically display an absence of inflammation despite containing high titers of live virus. Despite this curious presentation, MCV is very poorly characterized in terms of host-pathogen interactions. The absence of inflammation around MCV lesions suggests the presence of potent inhibitors of human antiviral immunity and inflammation. However, only a small number of MCV immunomodulatory genes have been characterized in detail. It is likely that many more remain to be discovered, given the density of such sequences in other poxvirus genomes. NF-κB activation occurs in response to both virus-induced pattern recognition receptor (PRR) signaling and cellular activation by virus-induced proinflammatory cytokines like tumor necrosis factor and interleukin-1. Activated NF-κB drives cytokine and interferon gene expression, leading to inflammation and virus clearance. We report that MC005, which has no orthologs in other poxvirus genomes, is a novel inhibitor of PRR- and cytokine-stimulated NF-κB activation. MC005 inhibited NF-κB proximal to the IκB kinase (IKK) complex, and unbiased affinity purification revealed that MC005 interacts with the IKK subunit NEMO (NF-κB essential modulator). MC005 binding to NEMO prevents the conformational priming of the IKK complex that occurs when NEMO binds to ubiquitin chains during pathway activation. These data reveal a novel mechanism of poxvirus inhibition of human innate immunity, validate current dynamic models of NEMO-dependent IKK complex activation, and further clarify how the human-adapted poxvirus MCV can so effectively evade antiviral immunity and suppress inflammation to persist in human skin lesions.